Aspergillus sibiricus (Aspergillaceae, Eurotiales), a novel acid-tolerant species in Aspergillus section Fumigati - Iliushin, Vadim A. (Phytotaxa, 2022)
A novel species in Aspergillus section Fumigati is described as Aspergillus sibiricus. The new species was isolated from an open coal mine in Altai, Siberia, Russia and is represented by ex-type strain CBS 143307. We used a polyphasic taxonomic approach to characterise the species. A description based on morphological features is provided and shows that the new species differs morphologically from closely related species (A. assulatus, A. nishimurae and A. waksmanii). Partial sequences of the loci encoding β-tubulin (BenA), calmodulin (CaM), ribosomal polymerase II second largest subunit (RPB2) and internal transcribed spacer rDNA region (ITS1-5.8S-ITS2) were analyzed as well. Sequences data, macro- and micromorphological and physiological characteristics distinguish A. sibiricus from all known species in section Fumigati, series Unilaterales. A. sibiricus, isolated from an acidic habitat (pH 3.2–3.4), is able to grow at pH 2 and is considered an acid-resistant species.